Remnants of an Ancient Deltaretrovirus in the Genomes of Horseshoe Bats (Rhinolophidae) - Hron, Tomáš; Farkašová, Helena; Gifford, Robert J; Benda, Petr; Hulva, Pavel; Görföl, Tamás; Pačes, Jan; Elleder, Daniel (Viruses, 2018)
Endogenous retrovirus (ERV) sequences provide a rich source of information about the long-term interactions between retroviruses and their hosts. However, most ERVs are derived from a subset of retrovirus groups, while ERVs derived from certain other groups remain extremely rare. In particular, only a single ERV sequence has been identified that shows evidence of being related to an ancient Deltaretrovirus, despite the large number of vertebrate genome sequences now available. In this report, we identify a second example of an ERV sequence putatively derived from a past deltaretroviral infection, in the genomes of several species of horseshoe bats (Rhinolophidae). This sequence represents a fragment of viral genome derived from a single integration. The time of the integration was estimated to be 11-19 million years ago. This finding, together with the previously identified endogenous Deltaretrovirus in long-fingered bats (Miniopteridae), suggest a close association of bats with ancient deltaretroviruses.
Keywords: Endogenous Retroviruses; koncové repetice; Animals; Chiroptera; evolution; Genomics; Terminal Repeat Sequences; Deltaretrovirus; genom; Genome; endogenous retrovirus; Evolution, Molecular; molekulární evoluce; Phylogeny; retrovirus; Recombination, Genetic; endogenní retroviry; bats; genomics; zvířata; fylogeneze; rekombinace genetická; genomika